Improving ethanol tolerance of ethyl carbamate hydrolase by diphasic high pressure molecular dynamic simulations - Qijia Zan; Mengfei Long; Nan Zheng; Zehua Zhang; Huimin Zhou; Xinjie Xu; Tolbert Osire; Xiaole Xia (AMB Express, 2023)
Key points 1 Diphasic high pressure molecular dynamic simulations were applied for ration engineering of ethyl carbamate hydrolase with improved ethanol tolerance. 2 The specific activity of H68A/K70R/S325N was 3.42-fold higher than WT. 3 The tolerance of triple mutant H68A/K70R/S325N to 20%(v/v) ethanol was increased to 41.16%, which was 5.02-fold higher than WT.